TiCl4 mediated facile synthesis of 1, 3, 4-oxadiazoles and 1, 3, 4-thiadiazoles. Issue 3 (1st February 2020) - Zhang, Lin; Yu, Yu; Tang, Qiang; Yuan, Jianyong; Ran, Dongzhi; Tian, Binghua; Pan, Tao; Gan, Zongjie
Abstract: An efficient method for the synthesis of 2, 5-disubstituted 1, 3, 4-oxadiazoles and 1, 3, 4-thiadiazoles has been developed. Various hydrazides or thionyl hydrazides readily react with DMA derivatives in the presence of TiCl4 as a catalyst to afford the desired products. This protocol provides a simple and economical procedure that affords the target products with good yields and wide substrate scope. GRAPHICAL ABSTRACT: